2015
DOI: 10.1021/acs.inorgchem.5b02262
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Mechanistic Studies Guiding the Rational Design of Molecular Electrocatalysts for Production and Oxidation of Hydrogen

Abstract: Understanding how to control the movement of protons and electrons is crucial to the design of fast, efficient electrocatalysts for H2 production and oxidation based on earth-abundant metals. Our work seeks to address fundamental questions about proton movement. We have demonstrated that incorporating a pendant amine functioning as a proton relay in the second coordination sphere of a metal complex helps proton mobility, resulting in faster and more energy-efficient catalysts. Proton-transfer reactions can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 129 publications
0
72
0
Order By: Relevance
“…Bidirectional catalysts typically operate at low overpotentials, in this case possibly facilitated by concerted PCET. 375,376 It was later found that the HER activity of the Ni complexes is greatly enhanced by using a “P 2 N” ligand, a seven-membered analogue of “P 2 N 2 ” ligands bearing only one NR′ substituent. When R = R′ = Ph, [Ni(P 2 N) 2 ] mediates the HER from protonated N,N-dimethylformamide (p K a = 6.1) extremely rapidly (TOF > 100 000 s −1 at −1.13 vs Fc +/0 ), albeit at a high overpotential ( η = 625 mV).…”
Section: [Nife]-h2asesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bidirectional catalysts typically operate at low overpotentials, in this case possibly facilitated by concerted PCET. 375,376 It was later found that the HER activity of the Ni complexes is greatly enhanced by using a “P 2 N” ligand, a seven-membered analogue of “P 2 N 2 ” ligands bearing only one NR′ substituent. When R = R′ = Ph, [Ni(P 2 N) 2 ] mediates the HER from protonated N,N-dimethylformamide (p K a = 6.1) extremely rapidly (TOF > 100 000 s −1 at −1.13 vs Fc +/0 ), albeit at a high overpotential ( η = 625 mV).…”
Section: [Nife]-h2asesmentioning
confidence: 99%
“…The high efficiency of H 2 ases requires that each catalytically active state be of similar free energy 375 and exist in an almost flat free energy landscape in which kinetic barriers to H 2 oxidation or evolution are minimized. 141 Reproducing these rates in synthetic systems will necessitate more rigid complexes, and no doubt motivate the synthesis of new polydentate ligands.…”
Section: [Nife]-h2asesmentioning
confidence: 99%
“…Hydrogenases are enzymes that can reversibly oxidize hydrogen with high efficiencies in nature. Inspired by these enzymes Bullock, DuBois and collaborators, developed complexes based on Ni, Fe, and Mn for the electrocatalytic oxidation of molecular hydrogen. All complexes are based on a P R 2 N R′ 2 cyclic 1,5‐diaza‐3,7‐diphosphacyclooctane ligand (R, R′ represent alkyl or aryl groups), that has pendent amines in close proximity to a vacant coordination site on the metal, leading to bifunctional activation of H 2 during the heterolytic cleavage of the H–H bond, mimicking the structure of the [Fe‐Fe] hydrogenase enzymes.…”
Section: Hydrogen Oxidation Reaction With Organometallic Complexesmentioning
confidence: 99%
“…12 These catalysts are bioinspired in that they incorporate the concept of a proton relay positioned near the metal center from hydrogenase enzymes but do not mimic the specific structure of the active site. The popular Ni(P 2 N 2 ) 2 hydrogen-evolving catalysts, as depicted in Figure 1d, have been particularly successful in terms of high turnover frequencies at relatively modest overpotentials.…”
Section: Molecular Electrocatalyst Designmentioning
confidence: 99%
“…The popular Ni(P 2 N 2 ) 2 hydrogen-evolving catalysts, as depicted in Figure 1d, have been particularly successful in terms of high turnover frequencies at relatively modest overpotentials. 12 Theoretical calculations have provided guidance for the modification of the ligands to alter the p K a ’s of the pendant amine and the metal center, as well as the reduction potentials, in ways that enhance the turnover frequency.…”
Section: Molecular Electrocatalyst Designmentioning
confidence: 99%